21) Solve quadratic equation 3x²-5x + 2 = 0 using formula.
Answers
Answer:
Complete step-by-step answer:
Step 1: Here the quadratic equation is given as 3x2−5x+2=0. In above equation, the coefficient of x2 is 3 so the value ofa=3, coefficient of x is −5 so the value of b=−5 and the constant term is 2 so the value of c=2 .
# ItzSabjeWaleSister
EXPLANATION.
Method = 1.
Quadratic equation.
3x² - 5x + 2 = 0.
As we know that,
Factorizes the equation into middle term splits, we get.
3x² - 3x - 2x + 2 = 0.
3x(x - 1) - 2(x - 1) = 0.
(3x - 2)(x - 1) = 0.
x = 2/3 and x = 1.
Method = 2.
⇒ 3x² - 5x + 2 = 0.
As w know that,
⇒ D = Discriminant Or b² - 4ac.
⇒ D = (-5)² - 4(3)(2).
⇒ D = 25 - 24.
⇒ D = 1.
⇒ α = - b + √D/2a.
⇒ α = -(-5) + √1/2(3).
⇒ α = 5 + 1/6.
⇒ α = 6/6 = 1.
⇒ β = - b - √D/2a.
⇒ β = -(-5) - √1/2(3).
⇒ β = 5 - 1/(6).
⇒ β = 4/6 = 2/3.
MORE INFORMATION.
Conjugate roots.
(1) = If D < 0.
One roots = α + iβ.
Other roots = α - iβ.
(2) = If D > 0.
One roots = α + √β.
Other roots = α - √β.